Scientific Opinion on an application by DOW AgroSciences LLC (EFSA‐GMO‐NL‐2010‐89) for placing on the market the genetically modified herbicide‐tolerant maize DAS‐40278‐9 for food and feed uses, import and processing under Regulation (EC) No 1829/2003. (5th December 2016) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Maize DAS‐40278‐9 was developed by direct Whiskers‐mediated transformation to express the aryloxyalkanoate dioxygenase‐1 (AAD‐1) protein, conferring tolerance to 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) and aryloxyphenoxypropionate (AOPP) herbicides. The molecular characterisation of maize DAS‐40278‐9 did not raise safety issues. The agronomic, phenotypic and compositional characteristics of maize DAS‐40278‐9 tested under field conditions revealed no differences between maize DAS‐40278‐9 and its non‐genetically modified (GM) comparator that would give rise to food and feed or environmental safety concerns. There were no concerns regarding the potential toxicity and allergenicity of the newly expressed protein AAD‐1, and no evidence that the genetic modification might significantly change the overall allergenicity of maize DAS‐40278‐9. The nutritional characteristics of maize DAS‐40278‐9 are not expected to differ from those of non‐GM maize varieties and no post‐market monitoring of food/feed is considered necessary. Maize DAS‐40278‐9 is as nutritious as its non‐GM comparator and other non‐GM commercial varieties. There are no indications of an increased likelihood of establishment and spread of occasional feral maize DAS‐40278‐9 plants, unless these plants are exposed to the intended herbicides. However, this will not result in different environmental impacts compared to conventional maize. Considering the scope of the application, interactions with the biotic and abiotic environment were not considered an issue. Risks associated with the unlikely but theoretically possible horizontal gene transfer from maize DAS‐40278‐9 to bacteria were not identified. The post‐market environmental monitoring plan and reporting intervals are in line with the scope of the application. In conclusion, the EFSA GMO Panel considers that the information available for maize DAS‐40278‐9 addresses the scientific comments raised by the Member States and that maize DAS‐40278‐9, as described in this application, is as safe as the non‐GM comparator and non‐GM maize reference varieties with respect to potential effects on human and animal health and the environment in the context of the scope of this application.